2013
DOI: 10.1587/transele.e96.c.686
|View full text |Cite
|
Sign up to set email alerts
|

Native Oxide Removal from InAlN Surfaces by Hydrofluoric Acid Based Treatment

Abstract: SUMMARYWe investigated the effects of chemical treatments for removing native oxide layers on InAlN surfaces by X-ray photoelectron spectroscopy (XPS). The untreated surface of the air exposed InAlN layer was covered with the native oxide layer mainly composed of hydroxides. Hydrochloric acid treatment and ammonium hydroxide treatment were not efficient for removing the native oxide layer even after immersion for 15 min, while hydrofluoric acid (HF) treatment led to a removal in a short treatment time of 1 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
2
2
0
Order By: Relevance
“…Here the spectrum for the SiO 2 /InAlN interface was obtained at u ¼ 908, for which the photoelectron escape depth was 2.9 nm. The energy position, shape, and intensity of the O 1s spectrum from the InAlN surface before deposition, immediately after the BHF treatment, coincided with those for the O 1s spectrum from the HF-treated gold surface, which indicated that the corresponding component can be attributed to absorbed water molecules [20]. On the other hand, as shown in Fig.…”
supporting
confidence: 60%
“…Here the spectrum for the SiO 2 /InAlN interface was obtained at u ¼ 908, for which the photoelectron escape depth was 2.9 nm. The energy position, shape, and intensity of the O 1s spectrum from the InAlN surface before deposition, immediately after the BHF treatment, coincided with those for the O 1s spectrum from the HF-treated gold surface, which indicated that the corresponding component can be attributed to absorbed water molecules [20]. On the other hand, as shown in Fig.…”
supporting
confidence: 60%
“…As we have reported previously [7], the native oxide layer at the as-served InAlN surface consists of oxides and hydroxides of In and Al as shown in Fig. 4 Fig.…”
Section: Introductionsupporting
confidence: 53%
“…Thus, it is highly likely that the polycrystalline state of the annealed Al 2 O 3 layer affected the electrical properties for sample B. If the grain boundaries generated by uncontrolled polycrystallization are concentrated, a leakage current path is possibly generated [7]. For sample B, we found that the magnitude of the leakage current was dependent on the measurement position even on the same chip, as shown for the worst and the best cases in Fig.…”
Section: Contributedmentioning
confidence: 68%
“…1(a). Prior to the deposition of Al 2 O 3 , the native oxide layer on the air-exposed InAlN surface was removed by hydrofluoric acid solution followed by rinsing in deionized water [22]. The Al 2 O 3 layer was formed by ALD at 350 • C using H 2 O and trimethylaluminum.…”
Section: Methodsmentioning
confidence: 99%